Peningkatan kemampuan pengembangan diri melalui media kujaga diriku bagi peserta didik tunagrahita kelas XI di SLB YAAT Surakarta - Apria Faizal; Erma Kumala Sari; Fadhilah Kusniati (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2025)
Students with intellectual disabilities have cognitive limitations that affect their ability to understand self-development concepts, particularly in recognizing which parts of the body may or may not be touched by others. Based on a needs analysis conducted at SLB YAAT Surakarta, it was found that students struggled to comprehend this material due to a lack of appropriate and engaging learning media. The primary aim of this study is to describe the initial conditions of the students, design a learning program, and evaluate the effectiveness of the Kujaga Diriku animated media in improving the understanding of body protection among students with intellectual disabilities. This study employs a quantitative approach with a quasi-experimental design, using pretests and posttests administered to a group of students to determine the impact of the media on learning improvement. Data were analyzed using descriptive and inferential statistical techniques to examine differences in learning outcomes before and after the intervention. The results show that the Kujaga Diriku animated media had a significant effect in enhancing the understanding of students with intellectual disabilities, while also contributing to a more engaging and interactive learning atmosphere.